2019
DOI: 10.1177/1071100719833993
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of the Combined Mechanism Ankle Support on Static and Dynamic Postural Control of Chronic Ankle Instability Patients

Abstract: Background: Chronic ankle instability (CAI) is associated with postural control impairment. Orthotic devices are routinely used to improve postural control of CAI patients and prevent recurrence of ankle sprain. This study aimed to evaluate and compare the effect of combined mechanism ankle support (CMAS) with soft ankle support (SAS) and custom-molded foot orthosis (CFO) on static and dynamic postural control in patients with CAI. Methods: Twenty-two patients with CAI and 22 matched healthy subjects were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 37 publications
4
24
0
Order By: Relevance
“…The results of the present study document a significant effect of soft and semirigid orthoses on balance performance of patients with CAI, in agreement with other studies 20,22,23 which found that both soft and semirigid orthoses reduced postural sway and improved reach distance in the SEBT in patients with functional ankle instability. Our results are also in line with those of Faraji et al 16 and Baier and Hopf, 4 who studied the effects of soft and semirigid orthoses on dynamic and semidynamic postural stability of patients with CAI, and found significant improvements in both outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study document a significant effect of soft and semirigid orthoses on balance performance of patients with CAI, in agreement with other studies 20,22,23 which found that both soft and semirigid orthoses reduced postural sway and improved reach distance in the SEBT in patients with functional ankle instability. Our results are also in line with those of Faraji et al 16 and Baier and Hopf, 4 who studied the effects of soft and semirigid orthoses on dynamic and semidynamic postural stability of patients with CAI, and found significant improvements in both outcomes.…”
Section: Discussionsupporting
confidence: 93%
“…The eight lines—anterior (A), posterior (P), medial (M), lateral (L), anterolateral (AL), anteromedial (AM), posterolateral (PL), and posteromedial (PM)—were constructed based on the direction shown in Figure 2 . Reach direction order was designed using a Latin square to avoid any order sequence effect that might contaminate the data [ 27 ]. Subjects performed two practice trials in each direction with a ten-second rest break between reach trials [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…All studies included had examined dynamic balance with and without ankle braces in individuals with and/or without CAI. One study included soft, 17 5 studies included semiriged, 15,17,19,20,22 5 studies included lace-up ankle braces, 15,18,[20][21][22] and one study included combined mechanism ankle support. 19 Four studies included participants with CAI, 17,19-21 while 5 included healthy participants.…”
Section: General Characteristicsmentioning
confidence: 99%
“…One study included soft, 17 5 studies included semiriged, 15,17,19,20,22 5 studies included lace-up ankle braces, 15,18,[20][21][22] and one study included combined mechanism ankle support. 19 Four studies included participants with CAI, 17,19-21 while 5 included healthy participants. 15,[17][18][19]22 Four studies examined dynamic balance using the SEBT/YBT.…”
Section: General Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation